High-efficient up-conversion of photoluminescence in CdSe quantum dots grown in ZnSe matrix - Strelchuk, V.V.; Valakh, M.Ya.; Vuychik, M.V.; Ivanov, S.V.; Kop'ev, P.S.; Shubina, T.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The intensive up-conversion photoluminescence at low temperatures in CdSe/ZnSe structures with single CdSe inserts of the nominal thickness 1.5 monolayer was observed. Excitation power dependensies show a nearly quadratic character up-converted photoluminescence signal from CdSe quantum dots. Up-conversion photoluminescence mechanism was interpreted on the basis of a non-linear process of two-step two-photon absorption through deep defect states including cation vacancies localized at the interface of quantum dots. This observation of photoluminescence up-conversion demonstrates the influence of quantum dot environment on its properties.